Contribution to the fauna and bionomics of entomophagous insects feeding on the small spruce bark beetle Ips amitinus (Eichh.) (Coleoptera, Curculionidae: Scolytinae) in West Siberia - Kerchev, Ivan Andreevich; Babenko, Andrey S.; Krivets, Svetlana A.; Krivosheina, M. G.; Smirnov, N. A.; Tselikh, E. V. (Entomological review)
A total of 29 species of entomophagous insects from 15 families of 4 orders were found for the fi rst time in the galleries of the small spruce bark beetle Ips amitinus within its invasive range in West Siberia; 26 species were predators of Ips amitinus, including 11 species of obligate and 15 species of facultative zoophages. The most abundant obligate predators were Thanasimus femoralis (Zett.) (Coleoptera, Cleridae) and Medetera fasciata Frey (Diptera, Dolichopodidae); the most abundant facultative predator was Placusa complanata Er. (Coleoptera, Staphylinidae). The larval ectoparasitoids Dinotiscus eupterus (Walk.) and Rhopalicus tutela (Walk.) (Pteromalidae) and the endoparasitoid of adults Ropalophorus clavicornis (Wesm.) (Braconidae) develop on I. amitinus both in its native range and in the secondary ranges. Widespread representatives of the local fauna that have established new trophic links with I. amitinus absolutely predominate among its entomophages in West Siberia. The European species Phloeonomus sjoebergi A. Strand (Staphylinidae) and Epuraea dolosa Kir. (Nitidulidae) were found for the fi rst time in Siberia. Ips amitinus has been included in the prey spectrum of Medetera penicillata Neg., which is an obligate predator of Polygraphus proximus Blandf., another invasive bark beetle of Far Eastern origin.